Working Tools Of Primitive Time Period (In The Example Of The Monuments Of Central Asia) - Akbar Shoberdiyev (Peerian Journals Publishing, 2024)
This article talks about the tools used by people of the primitive gang period in their lifestyle. The effect of tools of labor on the change of thinking of primitive man, work in general and the thinking of ancient man as a result of it are discussed.
Keywords: Primitive society; the simplest working tools; forces of nature